STUDY OF EDUCATIONAL STATUS OF 5TH CLASS STUDENTS IN TEHSIL BAHU OF JAMMU DISTRICT (J&K) - Ali, Ramzan (International Journal of Psychosocial Rehabilitation, 2020)
In the present study the investigator have conducted the study on the educational status of the children studying in fifth standard in primary schools in Bahu tehsil of Jammu district, in this investigator has conducted the study among the 5th class students regarding educational status reading and comprehensive in English, moreover the investigator has collected the data from the 200 students with the help of self prepared tool including (capital and small letters of alphabets, words, sentences, small paragraph, short story, essay with comprehension questions) regarding educational status ‘reading and comprehensive in English’ the investigator approached the respondents on the individual baises, the collected data was based on sex-wise, school-wise, the results of the study indicates that there was the significant difference among the 5th class students regarding educational status ‘reading and comprehensive in English’